Pembelajaran Digital dalam Era Pendidikan 5.0 - Wuwung, Janny O. (Jurnal Ilmiah Wahana Pendidikan, 2025)
The development of digital technology has brought significant changes to the world of education. Digital learning has become an innovative solution to increase the effectiveness, efficiency, and accessibility of learning. This article discusses the concept of digital learning, its implementation methods, and the results and discussion regarding its impact on students and educators. The research method used is a desk study, analyzing various academic literature, journals, and previous research results. The results indicate that digital learning can increase student engagement, learning flexibility, and digital literacy skills. However, challenges that arise include limited infrastructure, gaps in technology access, and teacher preparedness. In conclusion, digital learning can be an effective strategy if balanced with policy support, improved teacher competency, and strengthened educational infrastructure.